tính
/\(\frac{-1}{10}\)/ \(-\)\(\left(\frac{1}{2}\right)^{^2}\)\(\div\)\(\frac{5}{9}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a= (\(\frac{2}{5}\)+\(\frac{2}{9}\)+\(\frac{2}{11}\)\(\times\)\(\frac{5}{7}\)\(+\frac{7}{9}\)\(+\frac{7}{11}\)\()\)
Bấm máy tính:
E = \(\frac{4}{3}+\frac{1}{4}+\frac{3}{5}:\frac{4}{5}\)
E = \(\frac{4}{3}+\frac{1}{4}+\frac{3}{4}\)
E = \(\frac{7}{3}\)
Vậy E = \(\frac{7}{3}\)
\(E=\frac{0,8:\left(\frac{4}{5}.1,25\right)}{0,64-\frac{1}{25}}+\frac{\left(1,08-\frac{2}{25}\right):\frac{4}{7}}{\left(6\frac{5}{9}-3\frac{1}{4}\right).2\frac{2}{17}}+\left(1,2.0,5\right):\frac{4}{5}\)
\(E=\frac{\frac{4}{5}:\frac{4}{5}:1,25}{\frac{16}{25}-\frac{1}{25}}+\frac{\left(\frac{27}{25}-\frac{2}{25}\right).\frac{7}{4}}{\left(\frac{59}{9}-\frac{13}{4}\right).\frac{36}{17}}+\frac{6}{5}.\frac{1}{2}.\frac{5}{4}\)
\(E=\frac{1:\frac{5}{4}}{\frac{3}{5}}+\frac{1.\frac{7}{4}}{\frac{119}{36}.\frac{36}{17}}+\frac{3}{4}\)
\(E=\frac{4}{5}.\frac{5}{3}+\frac{\frac{7}{4}}{7}+\frac{3}{4}\)
\(E=\frac{4}{3}+\frac{7}{4}.\frac{1}{7}+\frac{3}{4}\)
\(E=\frac{4}{3}+\frac{1}{4}+\frac{3}{4}\)
\(E=\frac{4}{3}+1=\frac{7}{3}\)
Simplify 0.24*(-15)/4
Simplify 5/9/(1/11-5/22)+5/9/(1/15-2/3)
\(9\frac{2}{9}+\frac{2}{3}+7\frac{7}{9}\)
\(=9+\frac{2}{9}+\frac{2}{3}+7+\frac{7}{9}\)
\(=\left(9+7\right)+\left(\frac{2}{9}+\frac{7}{9}\right)+\frac{2}{3}\)
\(=16+1+\frac{2}{3}\)
\(=17+\frac{2}{3}\)
\(=\frac{51}{3}+\frac{2}{3}\)
\(=\frac{53}{3}\)
\(\frac{5}{9}.\frac{10}{11}+\frac{5}{9}.\frac{14}{11}-\frac{5}{9}.\frac{15}{11}\)
\(=\frac{5}{9}\left(\frac{10}{11}+\frac{14}{11}-\frac{15}{11}\right)\)
\(=\frac{5}{9}.\frac{9}{11}\)
\(=\frac{5}{11}\)
\(\left|\frac{-1}{10}\right|-\left(\frac{1}{2}\right)^2\div\frac{5}{9}\)
=\(\frac{1}{10}-\frac{1}{4}\times\frac{9}{5}\)
=\(\frac{1}{10}-\frac{9}{20}\)
=\(\frac{1\times2-9}{20}\)=\(\frac{-7}{20}\)